Evaluation of the effects of powdered cassava (Manihot esculenta) leaves on quality characteristics of pandesal (Salt bread). - Querubin, Rex Mauricio
The study aimed to develop a pandesal variant through the incorporation of cassava (Manihot esculenta) leaves. The effects of different weight ratios of powdered cassava leaves (PCL) to flour: 1:27, 2:26, 3:25, and 4:24 on the sensory attributes, physical properties, consumer acceptability, and proximate compositions of pandesal were evaluated. Based on the findings, pandesal with low PCL percentages have the greatest height and diameter, while pandesal with higher PCL percentages have the greatest weight and spread ratio. The results also revealed that pandesal with higher percentages of PCL have low acceptability in terms of color, aroma, taste, mouthfeel, and general acceptability. The formulation containing 3.75 percent PCL was the most preferred formulation (MPF); the pandesal rolls from this formulation have a brown color, a moderately sweet and yeasty aroma, a moderately sweet and salty taste, and a moderately soft mouthfeel. In terms of proximate composition, it was discovered that there was no significant difference in moisture and ash content between the MPF of pandesal added with PCL and malunggay pandesal. However, the addition of 3.75 percent PCL resulted in pandesal with higher moisture and ash content than conventional pandesal. The results of this study also revealed that the MPF of pandesal added with PCL has a lower unit yield than conventional pandesal and other existing pandesal variant. The MPF was also preferred by a higher percentage of consumers (55%) than malunggay pandesal. As a recommendation, the findings of incorporating PCL into pandesal bread will serve as a baseline database for future research aimed at improving existing food products and processes, as well as developing new ones.